THE EFFECT OF PHET VIRTUAL LABORATORY ON STUDENT PHYSICS LEARNING OUTCOMES: META-ANALYSIS - Sapitri, Zesmi Andestika (Universitas Negeri Padang, 2025)
Physics education in schools should be supported by experimental activities. One of the efforts to keep the experiment activities carried out is by utilizing virtual laboratory phet media in learning. This study aims to determine the influence of virtual laboratory phet media on students' physics learning outcomes. The moderator variables are the level of education, learning materials and learning models. This study uses a meta-analysis method that uses articles as a data source. Articles are collected from google scholar and publish or perish that have been accredited by sinta from the 2014-2024 range. From the collection, 41 decent article data were obtained. The article data obtained was analyzed with the help of JASP software and percentage techniques. The results of the analysis show that; 1) the influence of virtual laboratory phet on the overall student physics learning outcomes obtained a summary effect size of 1.122 very high categories, 2). The influence of virtual laboratory phet media on students' physics learning outcomes based on the highest level of education, namely at the high school level, the summary effect size of 1.176 is a very high category, 3). The influence of virtual laboratory phet media on students' physics learning outcomes based on the highest learning material, namely on collision, momentum and implus materials, the summary effect size is 1.572 in the very high category, 4). The influence of virtual laboratory phet media on student physics learning outcomes based on the highest learning model is in the PBL model with a summary effect size of 1.488 very high categories. Based on the results, teachers are advised to apply learning using virtual laboratory phet media at the high school level, especially on collision, momentum and implus materials with a cooperative learning model.